2022
DOI: 10.3390/v14071467
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution and Natural Recombination of Hepatitis D Virus: Implication of Kyrgyzstan Emerging HDVs in the Clinical Outcomes

Abstract: Discrepancies in human hepatitis delta virus (HDV) genotypes impact the virus’ biological behavior, clinical manifestation, and treatment response. Herein, this report aims to explore the role of recombination in the worldwide genotypic distribution and genetic diversity of HDV. Three-hundred-forty-eight human HDV full-length genomic sequences of ~1678 nt in length, isolated in twenty-eight countries worldwide between 1986 and 2018, were analysed. Similarity analysis and recombination mapping were performed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Regarding the amino acid sequences, the homologies among 9 HDV-2 S-HDAgs and L-HDAgs were found to be 85.2 % to 94.4 % and 86.0 % to 94.9 %, respectively. Notably, the HDV-2 and HDV-4 clones examined in this study were identified as belonging to the HDV-2a and HDV-4a subgenotypes ( Bahoussi et al., 2022 ; Le Gal et al., 2017 ).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Regarding the amino acid sequences, the homologies among 9 HDV-2 S-HDAgs and L-HDAgs were found to be 85.2 % to 94.4 % and 86.0 % to 94.9 %, respectively. Notably, the HDV-2 and HDV-4 clones examined in this study were identified as belonging to the HDV-2a and HDV-4a subgenotypes ( Bahoussi et al., 2022 ; Le Gal et al., 2017 ).…”
Section: Resultsmentioning
confidence: 77%
“…To investigate whether the editing structures of HDV-2 and HDV-4 are present in African HDV genotypes, we focused on HDV-5, which is genetically most similar to HDV-2 and has been found recently in Kyrgyzstan ( Bahoussi et al., 2022 ; Le Gal et al., 2017 ). We examined the editing structure of HDV-5 and analyzed four HDV-5 sequences, two of which belonged to subgenotype HDV-5a (GenBank accession numbers JX888103 and JA417556), and two to HDV-5b (LT594482 and LT604958).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] In addition, a high level of spread and diversity of HDV genotypes, with considerable intergenotypic and intragenotypic recombination, drives the emergence of new strains and subgenotypes as reported in recent study in Central Asia. [9] Worldwide distribution of HDV genotypes and subgenotypes HDV genotypes and subgenotypes display distinct geographical distribution (Figure 1). [8] HDV-1 genotype is the most prevalent worldwide, is found in nearly all continents, and has a distinct subgenotype distribution.…”
Section: Molecular Epidemiology Of Hdv Hdv Genotypes and Subgenotypesmentioning
confidence: 99%